Carbon dioxide storage in functional porous adsorbents - Er, Chen Kang (Nanyang Technological University, 2022)
The creation of energy, heating, cooling, and desalting of water are the most important demands for humans, whether for daily life or industrial activities. For many years, these requirements have been met mostly through the combustion of fossil fuels to generate electricity. However, the combustion of fossil fuels releases carbon dioxide (CO2) into the atmosphere, increasing CO2 concentrations, and greatly contributing to global warming. As a result, carbon capture and storage technology have gotten a lot of attention as one of the most promising mitigation strategies because of its capacity to capture CO2 from a power plant and store it in various ways. Researchers have introduced a new storage method known as adsorption, which utilized porous material heavily to capture and store CO2 under varying conditions such as temperature and pressure. Adsorption technology was widely used due to its low operating cost and reusable application after capturing CO2. To name a few porous adsorbents, activated carbon, silica gel, zeolite, and metal-organic frameworks (MOFs) have been widely researched as CO2 capture and storage adsorbents. MOFs have proved to be the most promising adsorbent mainly due to their tunable structure making it ideal to control their properties to capture CO2. This project aims to determine the carbon dioxide stored in MIL-101 (Cr), HKUST-1, and other modified MOFs (BMIMBr-MIL-101 (1:1), BMIMBr-MIL-101 (2:1), BMIMBr-MIL-101 (3:1), BMIMCl-MIL-101 (1:1), BMIMCl-MIL-101 (2:1)) under pressure up to 6bar and temperature of 298K using a volumetric set-up. MIL-101 (Cr) and HKUST-1 used in this experiment were synthesized beforehand and their surface characteristics are calculated by scanning electron microscopy (SEM), and thermogravimetric analyzer (TGA). Based on experimental results acquired, MIL-101 (Cr) had shown to have the highest gravimetric uptake of 0.20846g/g under 6 bar and 298K while HKUST-1 has a gravimetric uptake of 0.019839g/g under the similar conditions. After a comparison between these two MOFs, it is proven that MIL-101(Cr) had a higher potential in capturing more CO2 due to its high gravimetric and volumetric uptake. Hence, further studies and functionalization should be done on MIL-101(Cr) to enhance its adsorption capabilities to capture more carbon dioxide.